Tastes, Trade, and the Comparison of Structural Interdependence - Kleiman, Ephraim (Quarterly Journal of Economics, 1970)
I. Introduction, 279. — II. Degree of interdependence determined by technology and final demand, 280. — III. Effects of the trade structure, 281. — IV. Standardization for technology and for domestic demand, 283. — V. Results and conclusions, 285.